2018
DOI: 10.3390/toxins10070287
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Cardiovascular Uremic Toxicities

Abstract: Cardiovascular disease (CVD) remains a major cause of high morbidity and mortality in patients with chronic kidney disease (CKD). Numerous CVD risk factors in CKD patients have been described, but these do not fully explain the high pervasiveness of CVD or increased mortality rates in CKD patients. In CKD the loss of urinary excretory function results in the retention of various substances referred to as “uremic retention solutes”. Many of these molecules have been found to exert toxicity on virtually all orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 115 publications
(144 reference statements)
1
53
0
4
Order By: Relevance
“…In support of the notion that uremic toxins contribute to hypertension in CKD [ 12 , 20 ], our results demonstrated that maternal adenine-induced CKD mother rats exhibited hypertension related to elevated plasma levels of ADMA, SDMA, and TMAO. ADMA and SDMA are both uremic toxins, and their most well-known effect is the suppression of NO production [ 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…In support of the notion that uremic toxins contribute to hypertension in CKD [ 12 , 20 ], our results demonstrated that maternal adenine-induced CKD mother rats exhibited hypertension related to elevated plasma levels of ADMA, SDMA, and TMAO. ADMA and SDMA are both uremic toxins, and their most well-known effect is the suppression of NO production [ 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…1,2,10,68,69) Although the molecular basis for the correlation among indoxyl sulfate, eNOS, NO-related signaling, and ROS remains undefined in this study, future research should focus on the mechanisms underlying specifically impaired NO component in the rat superior mesenteric arteries by indoxyl sulfate. Several reports have suggested that the indoxyl sulfate levels in the circulatory system may increase under various conditions, including in CKD and diabetic nephropathy, 37,38,70) and impaired NO-mediated vasorelaxation was observed in both these diseases. 7,8,36) Thus, our findings indicate that indoxyl sulfate may be a causative factor for specifically impaired NO-mediated relaxation in such diseases; however, additional studies on the relationship among time course exposure of indoxyl sulfate, vascular function, and the development of complications in such pathophysiological states are required.…”
Section: Resultsmentioning
confidence: 99%
“…Reportedly, uremic toxins are accrued in chronic kidney disease (CKD) and display toxic effects on the blood and vessel wall. 7,[36][37][38] Various uremic toxins, mostly protein-bound, exert specific endothelial toxicity and cause endothelial dysfunction, including homocysteine, asymmetric dimethylarginine (ADMA), advanced glycation end products (AGEs), p-cresyl sulfate, and indoxyl sulfate. 7) Several studies have suggested a correlation between uremic toxins and endothelial function.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic and indolic compounds are products of catabolism of aromatic amino acids: phenylalanine, tyrosine and tryptophan are converted by the colonic bacteria to phenylacetate, p ‐cresol and indole, which are further conjugated with glutamine or sulfate in the gut mucosa and the liver to form phenylacetylglutamine, p ‐cresyl sulfate and indoxyl sulfate, respectively, and excreted in the urine. All these molecules are well‐known uraemic toxins which have been associated with CVD , particularly with chronic kidney disease , although their metabolic effects are largely unexplored. Phenylalanine and tyrosine microbial metabolism can also produce other phenolic metabolites such as phenylpropionic acids, phenyllactic acids or hippuric acid .…”
Section: Microbial‐derived Metabolites In Metabolic Health and Diseasementioning
confidence: 99%